Pengenalan Budaya Minum Jamu “BUMIMU” sebagai Penerapan Gerakan Nasional Bugar dengan Jamu (GERNAS BUDE JAMU) di SLB Purwosari Kudus - Yulia Pratiwi; Mera Putri Pratitis; Wildayanti Wildayanti; Aprillia Puspitasari Tunggadewi; Annis Rahmawaty; Luthfiana Nurulin Nafi’ah; Gunawan Firmansyah (BADAN PENERBIT STIEPARI PRESS, 2024)
Herbal medicine is one of Indonesia's cultural heritages that still survives and remains preserved. This healthy drink, originally made in Indonesia, is the people's choice. Jamu, as a herbal medicine that people have consumed for hundreds of years, needs to be labeled with a name for various purposes, such as people knowing the names of herbal medicine plants and at the same time people are aware of the biodiversity in the form of plants around them that have properties that are good for our bodies. Family Medicinal Plants (TOGA) can be used to make herbal medicine. This activity aims to introduce the cultivation of drinking herbal medicine as an implementation of the National Movement for getting fit with herbal medicine at SLB Purwosari Kudus. The results of the counseling can be seen from the increase in knowledge about herbal medicine as seen from the way the Purwosari Kudus SLB students answered with enthusiasm and interest in herbal medicine as traditional medicine.